B-catenin interaction with, and regulation of, integrin-linked kinase-1 in human oesophageal squamous cell carcinoma - Thomson, Bronwyn Mary (My University, 2011)
Integrin-linked kinase-1(ILK-1), an ankyrin repeat containing serine-threonine protein kinase, is highly overexpressed and aberrantly localised in several invasive carcinomas. The promoter region of the ILK-1 gene was examined by Melchoir et al (2002) and featured two T-cell factor-1 (Tcf-1) binding sites. Tcf transcription factors require β- catenin binding for activation of gene expression. The aim of this study was to determine whether these Tcf-1 sites interact with β-catenin and if so, are they essential to activate transcription of ILK-1. The role of β-catenin in the nucleus at a regulatory level and its influence on the protein levels of ILK-1 in moderately differentiated human oesophageal squamous cell carcinoma (HOSCC) cell lines were also examined. β-catenin and ILK-1 are key components in signal transduction pathways that when dysregulated lead to uncontrolled cell proliferation, one of the main hallmarks of cancer. This study shows that β-catenin and ILK-1 are expressed and localised in HOSCC cell lines as demonstrated by Western blotting. Evidence from co-immunoprecipitation assays indicates that β-catenin and Tcf-1 complex in the nucleus of a carcinoma derived from stratified epithelia such as the HOSCC cell lines under investigation. Electrophoretic mobility shift assays showed that the β-catenin/Tcf-1 complex binds to the two proposed binding sites in the ILK-1 promoter region. Therefore, it was reasonable to question whether this bound complex influenced ILK-1 expression levels. In order to increase expression of β-catenin within the HOSCC, the WHCO6 cell line was stably transfected with the pEGSH-β-catenin-pERV3 construct and stimulated with 1 μM and 2 μM of ponA respectively. However, when β-catenin levels were increased in a HOSCC cell line, it did not considerably affect ILK-1 expression levels. The tight regulatory mechanisms known to control β-catenin could possibly have masked the increase in β- catenin levels. Also the various degradation pathways of β-catenin have not been examined extensively within these cells lines and could possibly provide an explanation of the lack of a visually substantial increase of β-catenin and/or ILK-1. These results show that β-catenin and Tcf-1 complex in the nucleus and bind to the documented ILK-1 binding sites in the promoter region. This interaction does not influence the expression levels of ILK-1 in HOSCC cell lines. However, results presented in this study identify oesophageal squamous cell carcinoma as a prime candidate for β-catenin, Tcf-1 and ILK-1 specific immunotherapy.